Use of diuretics in hypertensive patients with metabolic disturbances - Yuliya Valer'evna Zhernakova (Системные гипертензии, 2013)
The multicenter research MERSY (Moxonidine Efficacy on blood pressure Reduction revealed in a metabolic SYndrome population) finished in 2008 was devoted to an assessment of long-term safety and efficiency of agonist I2-imidazolin receptors – moxonidine in patients with arterial hypertension and metabolic syndrome (in the general group and in advance defined subgroup of patients in a postmenopause). In 2013 final international results of the research MERSY which showed high antihypertensive activity of moxonidine, and also its positive influence on metabolic parameters and mass of a body were published.